Digital Governance and Green Business: Efforts to Realize Sustainable MSMEs in Pekanbaru City from an SDG Perspective - Mariaty Ibrahim; Mashur Fadli; Jeneva Augustin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the implementation of digital governance and green business practices as a means to foster sustainable Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City, viewed through the lens of the Sustainable Development Goals (SDGs). Digital transformation in governance and the adoption of eco-friendly business practices are crucial factors in enhancing MSME competitiveness while supporting inclusive and sustainable economic development. The study employs a qualitative approach with a descriptive method, utilizing in-depth interviews, observations, and document analysis involving MSME owners, local government officials, and relevant stakeholders. Data analysis was conducted through an interactive process of data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of digital governance has facilitated easier access to licensing services, business guidance, digital marketing, and business support for MSMEs. Meanwhile, the implementation of green business practices is becoming evident through the use of eco-friendly raw materials, energy efficiency, waste management, and heightened awareness regarding sustainable production practices. However, the implementation of these concepts still faces various challenges, such as limited digital literacy, restricted access to green financing, low technology adoption, and suboptimal synergy among stakeholders. The study concludes that integrating digital governance and green business practices contributes positively to achieving the SDGs—specifically Goal 8 (Decent Work and Economic Growth), Goal 9 (Industry, Innovation, and Infrastructure), Goal 11 (Sustainable Cities and Communities), Goal 12 (Responsible Consumption and Production), and Goal 13 (Climate Action). Therefore, strengthening policies, enhancing MSME capacity, and fostering collaboration among the government, the business sector, academia, and the community are essential to accelerate the development of competitive and sustainable MSMEs in Pekanbaru City.